2020
DOI: 10.1101/2020.02.23.961367
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The anticipation and perception of affective touch in women with and recovered from Anorexia Nervosa

Abstract: Disruptions in reward processing and anhedonia have long being considered as possible contributors to the aetiology and maintenance of Anorexia nervosa (AN). Recently, interoceptive deficits have also been observed in AN, including reduced tactile pleasure.However, the extent to which this tactile anhedonia is specifically liked to an impairment in a specialized, interoceptive C tactile system originating at the periphery, or a more top-down mechanism in the processing of pleasant tactile stimuli remains debat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 68 publications
(59 reference statements)
2
8
0
Order By: Relevance
“…This is particularly evident in psychopathology, for example in the contexts of eating disorders (EDs; Teaford et al, 2021 ). Indeed, ED patients present with profound alterations in body perception that include deficits in interoception and multisensory integration as well as abnormalities in body representation ( Crucianelli et al, 2020 ; Sacchetti et al, 2021 ; Teaford et al, 2021 ). Interestingly, these alterations in body perception have been found to be coupled with higher-order psycho-social impairments and specifically with difficulties in understanding others’ behaviors and emotions ( Caglar-Nazali et al, 2014 ; Bora and Köse, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly evident in psychopathology, for example in the contexts of eating disorders (EDs; Teaford et al, 2021 ). Indeed, ED patients present with profound alterations in body perception that include deficits in interoception and multisensory integration as well as abnormalities in body representation ( Crucianelli et al, 2020 ; Sacchetti et al, 2021 ; Teaford et al, 2021 ). Interestingly, these alterations in body perception have been found to be coupled with higher-order psycho-social impairments and specifically with difficulties in understanding others’ behaviors and emotions ( Caglar-Nazali et al, 2014 ; Bora and Köse, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies have recently shown that both acute and recovered AN (RAN) patients also display a reduced responsivity to the anticipation of CT-optimal touch, both in terms of neural response localized to the ventral mid-insula, and in terms of predicted pleasantness of touch [32,36]. Taken together, these findings suggest that in AN there is a dysregulation in the ability to correctly predict and interpret interoceptive stimuli, including CT-based pleasantness of touch.…”
Section: Introductionmentioning
confidence: 96%
“…CC-BY 4.0 International license perpetuity. It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted November 30, 2020. ; https://doi.org/10.1101/2020.11.30.403600 doi: bioRxiv preprint endures even after an otherwise successful recovery [31,32]. Anorexia Nervosa is a psychiatric condition characterised by profound disturbances in eating behaviours and body image [33], accompanied by impairments in social cognition and in the perception of interoceptive bodily sensations [34,35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several factors that might influence the perception of CT-optimal touch were taken into account, including the presence of mental disorders (Croy et al, 2016;Crucianelli, Cardi, Treasure, Jenkinson, & Fotopoulou, 2016;Crucianelli et al, 2020) , age (Sehlstedt et al, 2016), gender (Ilona Croy et al, 2014), and neurological and skin conditions (Liljencrantz & Olausson, 2014), Following Sailer and Ackerley (2019) "use it or lose it principle" we expected that an increase in touch deprivation would be related to a decrease in pleasantness ratings of CT-optimal touch videos.…”
Section: Introductionmentioning
confidence: 99%